PO 8394 South-south and north-south capacity strengthening within the screentb consortium: what have we learnt?. (24th April 2019) - Dockrell, Hazel; Schacht, Claudia; Walzl, Gerhard
Abstract : Background: Most research consortia and multicentre trials include capacity strengthening as one of their objectives. Activities are included in annual reports but the overall success or otherwise of these is hard to evaluate. Methods: The training and capacity building work package in the EDCTP2-funded ScreenTB Consortium includes support for the individual career development of young researchers. We have made mentoring the central activity, building on what we had learnt in the previous AE-TBC Consortium. We carried out formal training sessions and provided dedicated time-slots for meetings of mentee and mentor during annual meetings. We also introduced the concept of personal development plans through presentations and small group work. Results: Formal timetabled presentations and mentoring sessions have helped make capacity strengthening work. Challenges and solutions have been identified in group sessions and will be presented. This has enabled us to evaluate what works well and what is more challenging, when including capacity strengthening activities within a consortium with 5 African and 3 European partners. Conclusion: Dedicated time and commitment are required to make capacity strengthening work, but when it does, mentoring and personal development planning can provide both African and European researchers with an impartial opportunity to find solutions to their current challenges and to discuss their longer-term goals.